From Cooperation to Collaboration: Toward a Framework for Deepening Library Partnerships. Issue 5 (3rd July 2020) - Saunders, Laura; Corning, Sean
Abstract: Librarians are encouraged to collaborate in their work, but examples in LIS literature suggests the term "collaboration" is applied to a range of activities that vary widely in terms of interaction, resource-sharing, cooperative planning, and cooperative service delivery. Collaboration has been studied in other fields but remains largely unexplored beyond case studies in LIS. Through a series of focus groups with librarians and a range of potential community partners, this research identified barriers to collaboration and factors that enable successful partnerships, resulting in a general framework that could act as a guide to planning and developing deep collaborations.